The Early Use of Blinding in Therapeutic Clinical Research of Neurological Disorders - B. Jensen, Matthew; L. Janik, Erika; J. Waclawik, Andrew (Journal of Neurological Research And Therapy, 2016)
We sought to identify early uses of blinding in therapeutic clinical trials of neurological disorders by multiple search methods. A 1784 report by Benjamin Franklin and others described the evaluation of the use of Mesmerism to treat neurological and other syndromes including headache and epilepsy, using blindfolds and screens. This report demonstrated the usefulness of blinding to reduce bias in clinical research, yet despite this early discovery, blinding was not widely accepted or routinely used until the 20th century. Blinded clinical trials began to be used for various neurological syndromes in the 1950s, sporadically at first and then increasing in frequency in subsequent years. The reason for this delay is unclear, but we propose several hypotheses.
Keywords: neurology; research; clinical trial; blind; placebo